Preparation, characterization, and photocatalytic properties of Pt/BiOCl nanoplates - Yu, C.; Chen, J.; Cao, F.; Li, Xin Yong; Fan, Q.; Yu, J.; Wei, L. (2013)
A series of novel Pt/BiOCl nanoplate photocatalysts were synthesized by a photodeposition method. The as-synthesized products were characterized by N2 physical adsorption, X-ray diffraction, scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, photoluminescence (PL) emission spectroscopy, and UV-Vis diffuse reflectance spectroscopy (DRS). The photocatalytic activity of the samples was evaluated by photocatalytic degradation of acid orange II under both UV light (? = 254 nm) and visible light irradiation. The N2 physical adsorption test showed that the deposition of Pt nanoparticles could not produce obvious change in the specific surface area of the catalyst. The UV-Vis DRS results indicated that the presence of Pt nanoparticles could effectively increase the visible light absorption ability of Pt/BiOCl. The PL spectra indicated that Pt could effectively suppress the recombination of photogenerated hole-electron pairs of Pt/BiOCl. Activity tests showed that the deposition of Pt (1%-2%, mass fraction) greatly promotes the UV right photocatalytic activity. Pt also brought about an obvious visible light activity, which could be attributed to the visible light absorption and plasmon photocatalysis role of deposited Pt nanoparticles. © 2013, Dalian Institute of Chemical Physics, Chinese Academy of Sciences. Published by Elsevier B.V. All rights reserved.